Peran Program “Jumat Curhat” dalam Meningkatkan Citra Kepolisian Mojokerto Raya - Khoiru M Habibi; Rakhmad S. Ramadhani; Fatihatul L (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
The police are currently a topic of conversation due to several problems caused by irresponsible members, resulting in a negative view of the police. To overcome this, a Quick Wins Presisi program was implemented, such as "Friday Confide." This program is a response to problems in daily interactions between the police and the community, such as dissatisfaction with services, lack of communication, and transparency of police actions. "Friday Confide" is an initiative that aims to increase interaction between the community and the police by providing a platform for the community to convey complaints, aspirations and input directly. This research evaluates the effectiveness of the program and how the community responds and participates, especially in the Greater Mojokerto Police. The methodology used includes a descriptive qualitative approach with data collection through in-depth interviews, direct observation and related documentation. Using the Diffusion of Innovation theory, research shows that the "Friday Confide" program was well received by the people of Mojokerto as an effective place to convey aspirations and obtain information about police activities. However, researchers identified challenges such as limited time that hinders comprehensive communication and handling of issues, as well as the need for increased direct community involvement. This program has succeeded in improving relations and transparency between the police and the community, but requires adjustments such as extending time and strengthening follow-up. The research recommends ongoing evaluation of strategic adjustments to ensure programs continue to meet community needs and expectations.